Design of artificial metalloproteins/metalloenzymes by tuning noncovalent interactions - Hirota, Shun; Lin, Ying-Wu (Journal of biological inorganic chemistry, 2018)
Noncovalent weak interactions [hydrophobic interaction and hydrogen (H)-bond] play crucial roles in controlling the functions of biomolecules, and thus have been used to design artificial metalloproteins/metalloenzymes during the past few decades. In this review, we focus on the recent progresses in protein design by tuning the noncovalent interactions, including hydrophobic and H-bonding interactions. The topics include redesign and reuse of the heme pocket and other protein scaffolds, design of the heme protein interface, and de novo design of metalloproteins. The informations not only give insights into the metalloenzyme reaction mechanisms but also provide new reactions for future applications.